Effect of Micronutrients (B, Cu, Zn) on Growth and Yield of Rabi Groundnut under Drip and Mulch in Lateritic Soils of Konkan - KHETRE, O. S.; MAHADKAR, U.V.; GAME , V. N.; SUTAR, V. K. (Journal of the Indian Society of Coastal Agricultural Research, 2023)
.